The Influence of Mobile Technology Adoption Rate on GenZ Productivity in the Digital Era - Elvin Nury Khirdany; Wahyu Liana (Universitas Islam Kuantan Singingi, 2026)
The development of digital technology has brought significant changes to the lives of Generation Z, particularly in the use of mobile technology to support their daily activities. Mobile technology has now become a primary means of communication, learning, and accessing information in the digital age. This study aims to determine the effect of mobile technology adoption on Generation Z productivity in the digital age. The study was conducted on 100 Generation Z students aged 16–18 years using quantitative methods and questionnaires. The results show that the level of mobile technology use among Generation Z is relatively high and has a positive influence on student productivity, particularly in terms of ease of access to information, time efficiency, and daily learning activities. The results of the research test indicate that the level of mobile technology adoption has a significant effect on Generation Z productivity with an influence value of 61.8%. This indicates that the higher the use of mobile technology, the higher the productivity of Generation Z in the digital age. However, the use of mobile technology also needs to be controlled to avoid negative impacts such as distraction and digital addiction.